Remediation manual for contaminated sites - Russell, David L., 1942- (Taylor & Francis, 2012)
To ask the right question, one needs to have some idea of what the answer might be. So it is with remediation. There is no such thing as too much information when it comes to characterizing a site, as information can aid in selecting the best remediation options. Unfortunately, the collection of data for making an informed decision is often costly, forcing professionals to make decisions on incomplete data. The lack of accurate data can also lead to the wrong remediation method selections, unwanted surprises, and extra expense.Based on the author's more than 40 years of experi.